Sicurezza Territoriale e gestione delle emergenze: soluzioni ed architetture per sistemi collaborativi - Fiduccia, Andrea (GEOmedia, 2010)
Intergraph's solutions for Public Safety & Security, Critical Infrastructures Protection and Emergency Operation Centers Intergraph provides the world's leading public safety dispatch system, which is accessed by more than half a billion people worldwide when they dial for emergency response. Because coordination with public safety agencies during a large-scale event is so critical, Intergraph's Computer- Aided Dispatch (I/CAD) system forms the basis for interagency coordination and management of operations and serves as the foundation of the decision support process. I/CAD seamlessly integrates an interactive, realtime map display with call handling, dispatching, records and information management, remote and field access, analysis and models. Intergraph's systems meet IT security requirements – such as DIACAP – and dispatch interoperability (APCO, CAP) without compromising performance. Built on standard interfaces, Intergraph products I/Sight, I/Sensor and I/Alarm Plus allow two-way communication with a variety of video, sensor and alarm types (I/Security Framework). At the same time, Intergraph offers a broad range of solutions for Emergency Operations Centers (EOCs) and crisis management systems (I/PR, I2RMS, GIOTTO).